Pembelajaran Online Masa Pandemi Covid-19 Menggunakan Lesson Design Sebagai Strategi Pembelajaran dan Capaian Hasil Belajar Pada Hubungan Kelarutan dan Tetapan Hasil Kelarutan di SMAN 1 Singingi - Nofri Yuhelman; Dwi Putri Musdansi; Rosa Murwindra (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2022)
This research is the second research in the theme of Lesson Study-based Didactic Design. This research is based on the problem of learning difficulties and the low understanding of high school students on the concept of solubility and the solubility product constant. This study aims to make Lesson Design on the concept of solubility and solubility product constant in class XI SMA. This research was conducted at SMA Negeri 1 Singingi in class XI science and 2 chemistry teachers. The instruments used in this study were the TKR (Respondent Ability Test) questions, observation sheets and interview guidelines on the concept of solubility and solubility product constants. The method used in this research is a qualitative research method with a Didactic Research Design (DDR) approach. The research started from observation, interviews, and making TKR (Respondent Ability Test). The results of this study are the dissolution of the characteristics of the Learning Obstacle (LO) of students identified in the solubility concept and the probability of product being known. on the concept of solubility and the solubility product constant. Furthermore, the Learning Obstacles (LO) obtained were used to create online learning lesson designs during the Covid-19 pandemic. Lesson design used for teaching materials for teachers and a simple substitute for lesson plans